BUSINESS EDUCATORS’ RATINGS OF TEACHING STRATEGIES FOR IMPROVING STUDENTS’ ACADEMIC PERFORMANCE IN FINANCIAL ACCOUNTING IN COLLEGES OF EDUCATION IN SOUTH-EAST NIGERIA (NAU Journal of Technology and Vocational Education, 2024)
The study identified business educators’ ratings of teaching strategies for improvingstudents’ academic performance in financial accounting in colleges of education inSouth East Nigeria. Two research questions guided the study, while two nullhypotheses were tested at 0.05 level of significance. Descriptive survey researchdesign was adopted for the study. The population consisted of 84 business educatorsfrom colleges of education in South-East, Nigeria. Data was collected using a 17-itemvalidated questionnaire. The questionnaire was structured on a 5-point rating scale.The reliability of the instrument was ensured using pilot test technique, which wasanalyzed using Cronbach Alpha method that yielded an overall reliability co-efficientof 0.86. Data related to the research questions were analyzed using mean andstandard deviation, while z-test tools were used to test the null hypotheses. Thefindings revealed that cooperative and just-in-time learning strategies were rated at avery low extent. Gender did not affect business educators’ rating of cooperativelearning strategy while gender affected business educators’ ratings of Just-in-Timelearning strategy. It is concluded that teaching strategies for teaching financialaccounting in colleges of education in South-East Nigeria were rated at low extentand very low extent. It is also concluded that gender affected the ratings of just-intime learning strategy, while cooperative, learning strategy were not affected bygender. Based on the findings of the study, it was recommended that businesseducators should be mandated to apply the cooperative and Just-in-Time learningstrategies for teaching financial accounting in various colleges of education in SouthEast Nigeria to improve students’ academic performance. Business educators incolleges of education in South East Nigeria should be encouraged and educate theirfellow business educators on the importance and use of discovery learning strategy asa teaching strategy for improving students’ academic performance in financialaccounting. Most teachers should be coaxed to apply the Just‒in‒time teachingstrategy owing to the fact that they still give in to technophobia and also showincompetence in the use of modern teaching technologies.
Keywords: Business educators, teaching strategies, academic performance, financial accounting and colleges of education